2015
DOI: 10.1177/1932296815587938
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Glucose Sensor Symposium

Abstract: Hyperglycemia, hypoglycemia, and glycemic variability have been associated with increased morbidity, mortality, length of stay, and cost in a variety of critical care and non-critical care patient populations in the hospital. The results from prospective randomized clinical trials designed to determine the risks and benefits of intensive insulin therapy and tight glycemic control have been confusing; and at times conflicting. The limitations of point-of-care blood glucose (BG) monitoring in the hospital highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 135 publications
(311 reference statements)
0
3
0
Order By: Relevance
“…Because of the small sample size, their results should be interpreted with caution. Studies on exenatide as an adjuvant to other hypoglycemic agents have generated inconsistent results regarding whether exenatide could reduce GV parameters such as MAGE and SDBG [ 25 , 35 37 ]. Therefore, the ability of exenatide to effectively control overall GV is less certain at this point.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the small sample size, their results should be interpreted with caution. Studies on exenatide as an adjuvant to other hypoglycemic agents have generated inconsistent results regarding whether exenatide could reduce GV parameters such as MAGE and SDBG [ 25 , 35 37 ]. Therefore, the ability of exenatide to effectively control overall GV is less certain at this point.…”
Section: Discussionmentioning
confidence: 99%
“…In all participants, simultaneous monitoring of glucose and Holter ECG was performed. Within 4-day of informed consent, patients underwent CGM using the CGMS (Medtronic iPro2) [ 12 ], and Holter ECG monitoring was introduced 24-h after the start of CGM. CGM and Holter ECG were recorded during the next 48-h in parallel by synchronizing the timing of the devices.…”
Section: Methodsmentioning
confidence: 99%
“…If the patient’s serum glucose concentration is fluctuating, it may be necessary to measure glucose every 30 or 60 min[ 60 ]. Currently, technology for continuous blood glucose monitoring using vascular catheter blood sampling is currently undergoing clinical trials and may become the standard of care and can allow tighter glycemic control in addition to preventing severe hypoglycemia or hyperglycemia[ 61 ]. Research has shown promise, as the technology is capable of detecting changes in glycemia that may otherwise be missed in our current practice, and has shown that glucose levels correlate well with standard arterial glycemic measurement[ 62 - 64 ].…”
Section: Glycemic Control Therapymentioning
confidence: 99%